Bilateral reconstruction of the mandibular body with symphyseal preservation using a single fibula free flap: operative technique - Riccardo Nocini; Vittorio Favero; Luigi Chiarini; Pier Francesco Nocini (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Mandibular osteonecrosis may occur in 5% of the patients who undergo radiotherapy for the treatment of head and neck malignancies. Resection and microvascular reconstruction is the treatment of choice in complicated osteoradionecrosis, however multifocal presentation may complicate the management of the disease given the poor quality and limited availability of adequate recipient vessels. Operative technique A 74-year-old man affected by multifocal severe osteoradionecrosis of the mandible underwent bilateral resection of the mandibular bodies while preserving the symphysis. The defects were reconstructed with a single fibula flap composed by two bony segments connected by a central segment, corresponding to the symphyseal region, in which the bone was dissected and removed. The anastomosis was performed on a single side of the neck. Healing was uneventful and the adopted technique allowed for a quick functional and esthetic recovery. Conclusion The presented technique provided a safe and efficacious, although technically challenging, solution in a case presenting multifocal osteonecrosis of the jaw. The morbidity of the procedure was limited because the tissue resection and reconstruction processes were minimized. Graphical Abstract